Microcirculatory and metabolic changes in soft tissues in the dynamics of the wound process in explosive trauma with acute blood loss in an experiment - I. A. Shperling; M. V. Vinogradov; R. V. Semakin; N. V. Shperling; A. V. Shulepov; S. O. Rostovtsev; A. S. Kourov; M. V. Bazhenov (Сибирский научный медицинский журнал, 2021)
The aim of the study was to evaluate microcirculatory and metabolic changes in damaged skeletal muscles in rats with experimental explosive trauma with acute blood loss. Material and methods. An experimental model of explosive damage to the soft tissues of the pelvic limb in rats was used to assess microcirculation and metabolic activity in the muscles of the area of the explosive wound by laser Doppler flowmetry and laser fluorescence diagnostics using the LAKK-M device. Results and discussion. It was found that during the entire follow-up period (28 days), pronounced disorders of microcirculation and metabolism were formed in the damaged muscles. Tissue perfusion was significantly reduced, which is confirmed by a change in the coefficient of variation of the microcirculation index, the value of which was lower by 36–51 % (p < 0.05) in all follow-up periods in animals from the intact group, and the maximum decrease in the indicator was observed by 28 days (6.7 (6.3; 7.4) %, at p < 0.05). Tissue metabolism was rearranged in the direction of activation of the anaerobic pathway: there was a decrease in the index of specific oxygen consumption by the tissue – by 2.3 times (p < 0.05), the fluorescent index of oxygen consumption by the tissues – by 60 % (p < 0.05), the integral index of oxygen exchange efficiency by an average of 8.5 times (p < 0.05) relative to healthy animals, which generally indicated weak oxygen utilization by the tissues. These disorders of metabolism and oxygen consumption by the tissues of the damaged area persisted throughout the experiment with a slight positive dynamics by the end of the observation period. Conclusion. The obtained data are a pathogenetic justification for the development of means for  the local correction of microcirculatory and metabolic disorders in the muscles in the case of explosive trauma in the post-traumatic period.